Effects of photobiomodulation therapy combined to static magnetic field in strength training and detraining in humans: protocol for a randomised placebo-controlled trial. Issue 10 (28th October 2019) - de Paiva, Paulo Roberto Vicente; Casalechi, Heliodora Leão; Tomazoni, Shaiane Silva; Machado, Caroline dos Santos Monteiro; Vanin, Adriane Aver; Baroni, Bruno Manfredini; de Carvalho, Paulo de Tarso Camillo; Leal-Junior, Ernesto Cesar Pinto
Abstract : Introduction: In recent years, it has been demonstrated that photobiomodulation therapy (PBMT) using low-level laser therapy and/or light-emitting diode therapy combined to static magnetic field (sMF) has ergogenic effects, improving muscular performance and accelerating postexercise recovery. However, many aspects related to these effects and its clinical applicability remain unknown. Therefore, the aim of this project is to evaluate the ergogenic effects of PBMT/sMF in detraining after a strength-training protocol. Methods and analysis: The study will be a randomised, triple-blind, placebo-controlled clinical trial. Healthy male volunteers will be randomly distributed into four experimental groups: PBMT/sMF before training sessions + PBMT/sMF during detraining, PBMT/sMF before training sessions + placebo during detraining, placebo before training sessions + PBMT/sMF during detraining and placebo before training sessions + placebo during detraining. Strength-training sessions will be carried out over 12 weeks, and the detraining period will occur during the 4 weeks after. The muscular strength and the structural properties of quadriceps will be analysed. Ethics and dissemination: This study was approved by the Research Ethics Committee of Nove de Julho University. The results from this study will be disseminated through scientific publications in international peer-reviewed journals and presented at national and international scientific meetings. Trial registration number: NCT03858179 .